-5(2-2x)=2(x-3)+4

Simple and best practice solution for -5(2-2x)=2(x-3)+4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5(2-2x)=2(x-3)+4 equation:


Simplifying
-5(2 + -2x) = 2(x + -3) + 4
(2 * -5 + -2x * -5) = 2(x + -3) + 4
(-10 + 10x) = 2(x + -3) + 4

Reorder the terms:
-10 + 10x = 2(-3 + x) + 4
-10 + 10x = (-3 * 2 + x * 2) + 4
-10 + 10x = (-6 + 2x) + 4

Reorder the terms:
-10 + 10x = -6 + 4 + 2x

Combine like terms: -6 + 4 = -2
-10 + 10x = -2 + 2x

Solving
-10 + 10x = -2 + 2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.
-10 + 10x + -2x = -2 + 2x + -2x

Combine like terms: 10x + -2x = 8x
-10 + 8x = -2 + 2x + -2x

Combine like terms: 2x + -2x = 0
-10 + 8x = -2 + 0
-10 + 8x = -2

Add '10' to each side of the equation.
-10 + 10 + 8x = -2 + 10

Combine like terms: -10 + 10 = 0
0 + 8x = -2 + 10
8x = -2 + 10

Combine like terms: -2 + 10 = 8
8x = 8

Divide each side by '8'.
x = 1

Simplifying
x = 1

See similar equations:

| 4n+4=26 | | 2.1x+1.15y=2.30 | | 500=200+1.75 | | 24p^2-16p=0 | | 8-18x^2=0 | | 1x^2-16=0 | | -3(1-3b)-12=12 | | 5x+3+2x-4= | | -8x-17=3x-105 | | e=5n+8 | | 5x^2+8=4x^2-6x | | 25=-16t^2+35t+5 | | 8x^2=980 | | -3(3b+1)-12=12 | | (b^6c^2)-8= | | .20*65=x | | s+s+325000=550000000 | | s+s+32500=550000000 | | 2(2+2y)=19-3y | | s+s+325=550 | | -15-3x=-7x+45 | | F*0=6*0-1 | | 5xn-20=8 | | 14=1.5(7) | | 6(6+68)= | | n+36=56 | | 12s-12=9s-8 | | 6x+6=4x-2 | | 60x-60=144 | | n*5=95 | | 4m^2-227m-40=0 | | n-2=180 |

Equations solver categories